P029 Patient Perception and Clinical Impact of Direct-to-Consumer Advertising in Inflammatory Bowel Disease. (December 2019) - Gu, Phillip; Yang, Edward; Chittajallu, Punya; McNeill, Cathy; Singal, Amit; Kwon, John; Ahmed, Tasneem
Abstract : BACKGROUND: Direct-to-consumer drug advertising is a controversial marketing strategy that can potentially empower patients and/or negatively impact clinical practice and the patient-provider relationship. With an increasing number of available therapies for inflammatory bowel disease (IBD), little is known about patients' attitudes regarding IBD-related direct-to-consumer advertising (IBD-DTCA) and its impact on treatment decisions in clinical practice. We aim to characterize patient perception of IBD-DTCA and its impact on clinical decision making. METHODS: We administered a 58-item, mailed questionnaire to patients with IBD receiving Gastroenterology subspecialty care at a large academic health system. The survey assessed patient awareness and perception of IBD-DTCA and its effect on IBD treatment discussions and decisions. We used bivariate analysis to evaluate patient-level factors associated with awareness and favorable perception of IBD-DTCA. RESULTS: We achieved a response rate of 15.2% (n = 226 of 1486). Most patients (93.3%) reported awareness of IBD-DTCA, with adalimumab receiving the most exposure. A majority of respondents reported IBD-DTCA made them more aware of treatments they otherwise would not know about (53.6%), provided information in a balanced manner (63.5%), and taught them about new potential risks and side effects (64.5%). Patients without a college degree and those with a household income less than $75k per year perceived IBD-DTCA significantly more favorably. A minority of aware respondents reported IBD-DTCA made them less confident in their provider's judgement (12.3%) and that a treatment option was being withheld (6.6%). Finally, IBD-DTCA rarely changed IBD management, with only 7.6% of respondents having a discussion with their provider about the advertised drug and only two respondents (0.9%) being initiated on the advertised drug. CONCLUSION(S): IBD patients were aware of IBD-DTCA and perceived it favorably; however, IBD-DTCA rarely led to patient-provider discussions or changes in treatment regimen.